Transverse malocclusion, posterior crossbite and severe discrepancy - Brandão, Roberto Carlos Bodart [UNESP] (FapUNIFESP (SciELO), 2012)
This article reports the orthodontic treatment of a 14 years and 2 months old female patient, presenting both anterior and posterior unilateral left crossbite, related to a transverse atrophy of the maxilla and a severe negative tooth-arch discrepancy in the upper arch. A maxillary expansion with a modified Haas appliance was the first therapeutic attempt. Then, fixed appliances were used in both arches, and the second left premolar was extracted. The space for the upper left lateral incisor was achieved with compressed springs and tooth movement was accomplished with double archwires. The final result showed a good intercuspation, considering that the left molar relation remained as a Class II, which demanded special occlusal adjustments. This case was presented to the Brazilian Board of Orthodontics and Facial Orthopedics, representing category 5, as a partial requirement for the BBO certificate.
Keywords: Corrective orthodontics; Crossbite; Ectopic